A FORMATIVE EXPERIENCE IN THE PEDAGOGICAL INTERNSHIP: BLACK FEMALE HISTORICAL REPRESENTATION IN A CARD GAME - Rodrigues, Lillian [UNESP]; Custodio, Vagner Sergio [UNESP]; Simao, Lidiane [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This paper analyzed how the teacher can use the representativeness of women from Brazilian history as a methodological strategy, aiming to contribute to minimizing the impacts caused by ethnic and racial prejudices and limitations of gender roles. The hypothesis was that, taking female representativeness to the school environment, inequalities between genders can be minimized with the recognition and identification of female protagonism in important Brazilian historical moments, commonly related only to the male gender. The methodology used approached the story of historical characters portrayed in a book by means of a cards game with audio resources and field observations, reaching the qualitative result of improving students' self-esteem, self-image, and school performance, concluding that prejudice, coupled with gender-limiting roles, and low self-esteem can be factors associated with poor school performance and body image disorders.
Keywords: Representativeness; Card game; Pedagogical internship